Transcription of the human U2 snRNA genes continues beyond the 3' box in vivo. - Cuello, P; Boyd, D; Dye, M; Proudfoot, N; Murphy, S (1999)
The 3' box of the human class II snRNA genes is required for proper 3' processing of transcripts, but how it functions is unclear. Several lines of evidence suggest that termination of transcription occurs at the 3' box and the terminated transcript is then a substrate for processing. However, using nuclear run-on analysis of endogenous genes, we demonstrate that transcription continues for at least 250 nucleotides beyond the 3' box of the U2 genes. Although in vivo footprinting analysis of both the U1 and U2 genes detects no protein-DNA contacts directly over the 3' box, a series of G residues immediately downstream from the 3' box of the U1 gene are clearly protected from methylation by dimethylsulfate. In conjunction with the 3' box of the U1 gene, this in vivo footprinted region causes termination of transcription of transiently transfected U2 constructs, whereas a 3' box alone does not. Taken together, these results indicate that the 3' box is not an efficient transcriptional terminator but may act as a processing element that is functional in the nascent RNA.